2016
DOI: 10.1007/s11661-016-3565-9
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Investigation on Bending Deformation Behavior at Various Deflection Rates for Enhancement of Absorbable Energy in TRIP Steel

Abstract: Transformation-induced plasticity (TRIP) steel might have a high energy-absorption characteristic because it could possibly consume impact energy by not only plastic deformation but also strain-induced martensitic transformation (SIMT) during deformation. Therefore, TRIP steel is considered to be suitable for automotive structures from the viewpoint of safety. Bending deformation due to buckling is one of the major collapse modes of automotive structures. Thus, an investigation on the bending deformation behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The rate sensitivity of austenitic stainless steel is, thus, an important research object. Previous studies have described the rate sensitivity of mechanical characteristics in austenitic stainless steel; research works have also confirmed the mechanical properties of these materials per the strain‐induced martensitic transformation (SIMT) under inelastic deformation . In other words, SIMT is directly related to the reliability of the steel.…”
Section: Introductionmentioning
confidence: 94%
“…The rate sensitivity of austenitic stainless steel is, thus, an important research object. Previous studies have described the rate sensitivity of mechanical characteristics in austenitic stainless steel; research works have also confirmed the mechanical properties of these materials per the strain‐induced martensitic transformation (SIMT) under inelastic deformation . In other words, SIMT is directly related to the reliability of the steel.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the plastic behavior of these stainless steels has been extensively investigated to understand how the continuously reforming bi-phase material responds to the applied loads. Majority of the studies on the topic evaluated the two, kinetics of the phase transformation [1][2][3][4][5] and the hardening behavior of the material during transformation [2,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, another important issue would be the damage growth, decreasing of the load-carrying capability and fracture of the material during and after the phase transformation.…”
Section: Introductionmentioning
confidence: 99%
“…They must enable light weight construction by a combination of excellent mechanical properties yet at an affordable price [1][2][3]. To date, transformation-induced plasticity (TRIP) steels have been developed [4][5][6]. TRIP steels have a multi-phase microstructure, including polygonal ferrite, bainite, martensite and retained austenite (RA) [7].…”
Section: Introductionmentioning
confidence: 99%